Selective arylation of phenol protected propygyl bromide via pd-catalysed Suzuki coupling reaction: synthesis, mechanistic studies by DFT calculations and their pharmacological aspects - Farooq, Hira; Rasool, Nasir; Ansari, Muhammad Tayyab; Rizwan, Komal; Iqbal, Sarosh; Mahmood, Tariq; Israr, Hira; Ayub, Khurshid; Rasheed, Tahir; Seema, Zareen; Akhtar, Muhammad Nadeem (Polish Pharmaceutical Society, 2018)
Biaryls are the potential source of synthetic drugs. The present study describes the synthesis of a series of functionalized biphenyl derivatives (3a-3g) using Pd-catalyzed Suzuki coupling reaction. The experimental results revealed the facile synthesis of biphenyl derivatives (3a-3g) with notably high yield (80-88%). Density functional theory (DFT) studies were performed by Gaussian 09 software in order to rationalize the selectivity of coupling at C-Br bond instead of C-Cl bond. In addition of synthesis, the biological activities (biofilm inhibition, hemolytic and anti-thrombolytic) of these novel compounds were investigated. These results exhibited good biofilm inhibition (5.86-65.8%), hemolytic (1.32-30.1%) and anti-thrombolytic activities (9.64-42.5%), indicating the potential use of these compounds for pharmaceutical applications